(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Corneal thickness (CT) is an important parameter in refractive surgery but available data is scanty on corneal thickness of normal Malays. The purpose of this study is to determine central and peripheral CT in a sample of Malays and find its effect on age. Methods: Seventy–two (72) participants were invited to participate in this study. Their age ranged from 15 to 65 years old. CT was measured using an ultrasonic pachometer (Corneo-Gage TM Plus2) at 5 different locations namely central, superior, temporal, inferior and nasal regions of the cornea. A total of three readings were taken for each location of the cornea and the mean was calculated. CT was presented as total, epithelial and stromal thickness for three age groups, namely <20years, 21-40years and >40 years for comparison. Results: Mean value for central CT for Malays was 597.9 ± 35.2 μm and peripheral CT was significantly thicker than the centre at all locations. There was significant thinning in CT as age advanced at all locations except at the centre. The epithelial layers do not show any changes with respect to location and age which implied that changes in CT at different location and as results of advancing age were mainly due to the stroma. Conclusion: The values of CT in normal Malays was 597.9 ± 35.2 μm and CT was thinnest at the central region. Except at the central region CT decreased with advancing age. These values can be a suitable reference when planning for refractive surgery and penetrating keratoplasty among Malays. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.600-605